Strategi Efektif Mengintegrasikan Pembelajaran Sosial Emosional dalam Pembelajaran Abad Ke-21 - Nurvahana Nurvahana (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Social Emotional Learning (SEL) is increasingly recognized as a critical element in 21st-century education, focusing on non-cognitive competencies such as empathy, collaboration, and self-regulation. This literature-based study explores effective strategies for integrating SEL into educational practices. The findings highlight several key approaches, including thematic and project-based learning, fostering a positive school culture, ongoing teacher training, and the use of digital tools. These strategies not only support students’ emotional and social development but also enhance overall academic performance. The study concludes by emphasizing the need for comprehensive educational policies and professional development to ensure consistent and sustainable SEL implementation.